Chemical characteristics of snow cover in the high-latitude Russian Arctic (Baranov Cape, Bolshevik Island, Severnaya Zemlya) - O. V. Shevtsova; E. D. Dobrotina; A. B. Goncharova; A. P. Nedashkovsky (Лëд и снег, 2023)
For the first time, features of the chemical composition of the snow cover during its accumulation on the Bolshevik Island (the area of the research station «Cape Baranov» Ice base») were studied. In winter 2018/19, the following elements density, conductivity, total acidity, pH, NH4+, NO2-, NO3-, PO43-, and Si and, additionally, Na+, К+, Ca2+, Mg2+, Cl-, and SO42-, were measured in new and old snow. Regularities of changes in the parameters of these two types of snow with time have been found. New snow is characterized by negative time trends in density, pH, conductivity, and total acidity, and by positive ones – in NO3–. All statistically significant changing parameters of new snow, except NH4+, showed high temporal variability. In the old snow, trends of decreasing NO3– and total acidity and increasing pH with the depth in the snow cover, as well as a positive correlation between NO3– and NH4+ have been revealed, that is not typical for the new snow. It was shown that the ammonium content in the old snow was, on average, 2.8 times higher than in the new one. The influence of different natural and anthropogenic factors on the snow chemical composition on the Bolshevik Island is discussed. We show that the increase in the total acidity of snow up to 0.001–0.014 meq/l in November–June during the young ice formation and then freeze-up could be due to anthropogenic nitrogen and sulfur oxides in roughly equal proportions. However, the chemical composition of the studied snow corresponds to the zone of the ecological norm. We compared the chemical composition of snow on the Bolshevik Island with similar characteristics of precipitation in other background regions of the Russian Federation using data of the World Weather Watch of the World Meteorological Organization. It was revealed that the studied snow was more acidic, less mineralized, depleted in sulfates, ammonium, nitrates and contained low electrical conductivity. In comparison with the snow cover on the Golomyanny Island (Severnaya Zemlya), the studied old snow contained minimal amounts of basic ions and was more acidic.